Esthetic and function improvement by direct composite resins and biomimetic concept - Paschoal, Marco Aurélio [UNESP]; Santos-Pinto, Maria de Lourdes [UNESP]; Nagle, Maurício Meirelles [UNESP]; Ricci, Weber Adad [UNESP] (Jaypee Brothers Medical Publishing, 2014)
Aim: This case report describe a resin layering restorative technique based on biomimetic concept to improve esthetics in a patient with dental defects that affected both enamel and dentin in anterior teeth. Background: Severe structural defect in anterior teeth compromises esthetics and it is a high challenge to become the defect imperceptible after the restoration. Case description: A clinical sequence of applying different composite resin layers allowed the reproduction of the interaction between hard dental tissues and the restorative material. Conclusion: This technique achieved a satisfactory final esthetic outcome, preserving sound teeth structure and at same time, improved the quality of life of the young patient. Clinical significance: The utilization of the biomimetic concept to increase a disharmonic smile with dental defects is based in a conservative approach, which reached a satisfactory and esthetic outcome.
Keywords: Esthetics; Biomimetics; Composite Resins